Nonlinear convection and joule heating impacts in magneto-thixotropic nanofluid stratified flow by convectively heated variable thicked surface - Waqas, M.; Dogonchi, A.S.; Shehzad, S.A.; Khan, M. Ijaz; Hayat, T.; Alsaedi, A. (Journal of molecular liquids, 2020)
The modeling of magnetohydrodynamic (MHD) nonlinear convected flow of thixotropic non-Newtonian material is carried out in this piece of research. The aspects of Joule dissipation, heat generation and thermal radiation are considered to analyze the heat transportation analysis. The combination of stratified and convective conditions phenomenon is accounted first time. The model non-dimensional quantities are calculated with the help of optimal homotopy procedure. The optimal values of non-zero auxiliary constraints are calculated and visualized. We observed that the increasing values of radiation, Eckert and Biot numbers lead to higher profile of temperature and stronger thickness of temperature boundary-layer. Further, presence of thermophoretic and Brownian movement factors have opposite nature for nanomaterials concentration. •Nonlinear mixed convection flow bounded by variable thicked surface is formulated.•Magneto nanofluid with double stratification phenomena is considered.•Heat transfer captures thermal radiation, Joule heating and heat generation/absorption aspects.•The results are plotted and interpreted.•Homotopy algorithm is utilized for the computation of nonlinear systems.